Selektive intraarterielle Radiotherapie (SIRT) maligner Lebertumoren - Müller, Stefan P.; Ezziddin, Samer; Antoch, Gerald; Lauenstein, Thomas; Amthauer, Holger; Haug, Alexander R.; Bockisch, Andreas (Nuklearmedizin - NuclearMedicine, 2017)
These guidelines aim to support medical personnel and physicians working in oncology in selecting appropriate patients, in treatment planning, preparation and implementation of SIRT for the treatment of primary and secondary liver malignancies. The focus lies on the requirements in the treatment center with regard to staffing, technical, and organizational aspects including radiation safety. Patient selection need to be performed in an interdisciplinary tumor board including the medical team tasked with the treatment and a medical physics expert. The aims of the treatment, the workup necessary for patient selection and treatment planning, and for avoiding complications are presented as are the requirements for obtaining informed consent from the patient. The follow-up of patients after SIRT also requires interdisciplinary cooperation, including communication with the local family physician.
Keywords: Radioembolisation; SIRT; TARE; primäre Lebertumoren; Lebermetastasen; Yttrium-90